Solanesol: a promising natural product - Ma, Yinchao; Wei, Ge; Dong, Zhichen; Wang, Ziyuan; Zhai, Xinlong; Liu, Yuan; Chen, Huan; Fu, Yaning; Hou, Hongwei; Hu, Qingyuan; Chu, Ming (Frontiers in Pharmacology, 2025)
Solanesol, identified as Nonaprenol alcohol, predominates in the Solanaceae family. This compound exists as a white to pale yellow solid at room temperature, characterized by low polarity and water insolubility. Its unique chemical structure—featuring nine non-conjugated double bonds and low polarity—confers remarkable biological activities. Recent studies have demonstrated that solanesol exhibits polypharmacological properties, including antimicrobial, antioxidant, anti-inflammatory, and membrane-stabilizing effects. Mechanistically, solanesol suppresses ROS generation and inhibits pro-inflammatory cytokines (IL-1β, TNF-α). Preclinical studies highlight its therapeutic potential in inflammatory disorders (periodontitis, neuropathic pain) and neurodegenerative diseases (Alzheimer’s, Parkinson’s). However, current research still faces critical bottlenecks, such as a lack of in vivo pharmacokinetic data, unclear molecular targets, and insufficient toxicity assessments. Future studies urgently need to integrate experimental approaches, including target screening, nanotechnology-based delivery systems, and multi-omics analysis, to elucidate its mechanisms of action and promote clinical translation. As a compound that combines natural safety with multi-target effects, solanesol is not only a research focus for the development of novel drugs but also a bridge connecting natural products and precision medicine, poised to lead the innovation of next-generation biocompatible therapies.